PENGARUH SKIN TERHADAP IPR SUMUR PERFORASI PADA RESERVOIR DENGAN TENAGA DORONG GAS TERLARUT - Setiati, Rini
This research investigated IPR curve equation for perforated well. In this thesis , an IPR curve equation developed using three - phase , one dimension single well simulator combine with flow equation of perforation derived by Perez & Kelkar . Perez & Kelkar had derived an equation to predict pressure drop across perforation. To developing inflow performance in perforated well , a computer program has been prepared and the program has been run for varoius set of data. These data consist of reservoir data and perforation data , as well as perforation size and length, perforation radius and perforation density. Also the simulator used various data of skin factor, specific gravity oil and absolute permeability. The computer simulated data in two techniques of perforation , overbalanced perforation and ·underbalanced perforation. Comparison of the perforating techniques show that underbalanced perforation produces more potential well than overbalanced perforation, and open hole well produces more potential than perforated well. Using regression analysis , a new equation has been developed to calculate the IPR curve in the well which is perforated by overbalance and underbalance techniques. Comparison of the new equation to result from the simulator show excellent agreement: